The Performance Analysis of An AirGapped Transformer Used in Wireless Charging System - Ahmet Fenercioğlu (Journal of New Results in Science)
Abstract - This study included performance analysis studies of an EE core structured and air-gapped transformer which is operated under the network frequency for wireless charging battery of shuttle robots during duty. Proposed design is modelled analitycally and design is verified by 2 dimensional finite element analysis (FEA) and experiments. In this stage unloaded, full loaded, and short circuit analysis of model are simulated and performance is determined according to airgap distance. Primer and seconder currents, voltages, power factor, efficiency, active power, regulation and short-circuit ratios are examined by analysis and experiments. In FEA solutions, input power is 588,28 W, output power is 387,89 W, power factor is 0.31 , flux linkage 238,34.10-5,regulation is 30,88 %, short-circuit ratio is 70,78 % for 3 mm airgap distance.Airgapped transformers was used in wireless charge station (WCS) and tested. About 63 V voltage and 4.24 A current are applied to Pb-Ac battery group by WSC. 200 Wh energy is transferred wirelessly along 45 minutes.